Understanding the Position of Philosophy in Other Sciences - Zaskia Laela Safira; Silva Nurfadhillah; Alify Akila Putri (Penerbit Hellow Pustaka, 2026)
Philosophy holds a crucial position in the development of scientific knowledge as it functions as a conceptual foundation, a determinant of direction, and a regulator of the use of science. The presence of philosophy enables science to develop not only in practical and technical aspects but also to comprehend the dimensions of essence, purpose, and the underlying values. In the context of the philosophy of science, the discussion focuses on the historical development of science and technology, the nature and sources of knowledge, and the criteria of scientific truth. Through these studies, philosophy serves as a means of critical reflection on the processes and outcomes of scientific development. Furthermore, philosophy plays a guiding role in ensuring that science is applied ethically and responsibly in accordance with human values. Without a philosophical foundation, the advancement of science risks losing its orientation toward values and human purposes. Therefore, the integration of philosophy into the development of scientific knowledge is essential to ensure that science contributes not only to technological progress but also to human well-being and the sustainability of life. Thus, the philosophy of science provides a strategic contribution to shaping scientific knowledge that is critical, systematic, and oriented toward moral and social responsibility (Ghufron, 2023).